Leveraging University-Community Partnerships in Rural Georgia: A Community Health Needs Assessment Template for Hospitals - Ayanna Robinson; Sabrina Cherry; Michelle Elliott; Marsha Davis; Grace Bagwell (Georgia Southern University, 2016)
Background: Under the Affordable Care Act, nonprofit hospitals are required to conduct a Community Health Needs Assessment (CHNA) every three years. Using recommendations proposed by Georgia Watch, students and faculty members from the University of Georgia (UGA) conducted a CHNA for a hospital in a rural county in Georgia. The purpose of the CHNA was to identify community health problems and needs, as well as community assets and resources. The aim of this report is to describe the process for conducting the CHNA, the findings, and the lessons learned. Methods: The CHNA team consisted of students and faculty members from UGA's College of Public Health and a Public Service and Outreach professional who worked in the community. In completing the CHNA, the team used the following fivestep process: define community, collect secondary data on community health, gather community input and collect primary data, prioritize community health needs, and implement strategies to address community health needs. Primary and secondary data were collected. Results: By triangulating findings across data sources, the CHNA team created a community health profile for the service area of the hospital. Based on these findings, the community identified four main areas for improvement, prioritized these health issues, and developed an implementation strategy for the hospital and community. Conclusions: The process used to conduct this CHNA can serve as a model for other rural communities undergoing similar assessments. Lessons learned from completing this CHNA can be applied to future CHNA efforts.